ANALYSIS OF LEGAL PROTECTION FOR ONLINE SHOPPING CONSUMERS - I Putu Agus Putra Arimbawa; I Made Dedy Priyanto (Transpublika Publisher, 2024)
The study aimed to examine the legal safeguards provided to consumers engaged in online shopping. This study utilized a normative juridical approach with a descriptive qualitative method. Secondary data was collected through a literature review, encompassing various sources such as journals, books, laws, and regulations. The analysis was descriptive in nature, leading to a generalization of the research problem. The findings revealed that consumer protection is regulated by Law no. 8 of 1999 on Consumer Protection, with the ITE Law, specifically Law no. 19 of 2016 on Information and Electronic Transactions, also being applicable to online shopping transactions. Disputes arising from online shopping can be resolved through instant claims (negotiation, mediation, etc.), seeking assistance from the Consumer Dispute Settlement Agency, or resorting to legal action. Furthermore, the study highlighted the importance of consumer awareness and education in understanding their rights and responsibilities when engaging in online shopping. It also emphasized the need for e-commerce platforms to implement transparent and fair practices to protect consumers from fraudulent activities